2013
DOI: 10.1039/c2ta01338j
|View full text |Cite
|
Sign up to set email alerts
|

High performance LiV0.96Mn0.04PO4F/C cathodes for lithium-ion batteries

Abstract: The LiV 0.96 Mn 0.04 PO 4 F/C composite was prepared by partial substitution of vanadium with manganese and in situ carbon coating of LiVPO 4 F via a modified carbothermal reduction route. Rietveld refinement of X-ray diffraction (XRD) patterns shows that the crystalline lattice is smaller than the value reported in the literature. While electron energy loss spectroscopy (EELS) on a selected area of high resolution transmission electron microscopy (HRTEM) demonstrates that Mn is successfully doped into LiVPO 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Oxalic acid and PVDF are pyrolyzed to generate the amorphous pyrolytic carbon. The lattice parameters of LiV 1‐x Al x PO 4 F/C are similar to literatures ,. With the increasing of Al 3+ doping ratio, the lattice parameters ( a , b , c and V ) decrease gradually and lattice shrinks because the ionic radius of Al 3+ (53.5 pm) is smaller than that of V 3+ (64 pm).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Oxalic acid and PVDF are pyrolyzed to generate the amorphous pyrolytic carbon. The lattice parameters of LiV 1‐x Al x PO 4 F/C are similar to literatures ,. With the increasing of Al 3+ doping ratio, the lattice parameters ( a , b , c and V ) decrease gradually and lattice shrinks because the ionic radius of Al 3+ (53.5 pm) is smaller than that of V 3+ (64 pm).…”
Section: Resultssupporting
confidence: 82%
“…It can be found that the charge transfer resistance ( R ct ) drops gradually with the increasing of doping ratio, which decreases from 278.8 Ω (undoped sample) to 180.6 Ω, 132.5 Ω, 76.5 Ω and 67.1 Ω when the doping ratio x is 0.01, 0.02, 0.03 and 0.04. The R ct value of LiV 0.97 Al 0.03 PO 4 F/C is lower than literatures ,,. It presents an inverse relationship between conductivity and resistivity.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…By optimizing preparation conditions, the reversible capacity can be as high as 155 mAh/g with a small voltage polarization, which is very close to the theoretical capacity of 156 mAh/g [43]. Additionally, long-term cycling stability was achieved for LiV 0.96 Mn 0.04 PO 4 F, with a capacity retention of 90 % after 1000 cycles [44]. LiVPO 4 F exhibits high ionic conductivity but poor electronic conductivity [45].…”
Section: Fluorophosphatesmentioning
confidence: 82%
“…LiVPO 4 F has been widely investigated as a potential cathode material for LIBs operating at 4.2 V vs. Li/Li + . [ 61,383 ] Cyclability of a nanosized LiVPO 4 F/graphene composite (LVPF/G) synthesized via a facile mechano-chemical approach exhibited an initial charge capacity of 287 mAh g −1 at rate of 0.1 C (1 C = 310 mA g −1 ) with no capacity fading after 100 cycles and a good rate capability of 168 mAh g −1 at 10 C under 0.01-3 V vs. Li/Li + . [ 384 ] Roh et al [ 385 ] developed a LiTi 2 (PO 4 ) 3 /rGO nanocomposite with a NASICON-type structure that delivered a reversible …”
Section: (V Ti) 2 (Po 4 )mentioning
confidence: 99%